Victim detection platform in IoT paradigm. (23rd April 2019) - Hong, Minsung; Akerkar, Rajendra
Summary: The advent of Internet of Things (IoT) paradigm is having a great ripple effect in the field of disaster management as well as many other areas. Victim detection has been studied as rescuer‐ or victim‐oriented approach, which utilises the IoT advanced technologies, but they have weaknesses according to disaster types. In this paper, we propose a Victim Detection Platform (VDP) architecture combining both approaches using various advanced technologies such as IoT, drone and edge/cloud computing to offer higher quality services, which ultimately result in swifter, better responses and more lives saved. First, we have reviewed related literature regarding three crucial issues (ie, multi‐modal evaluation for reliable data, edge‐based real‐time response, and privacy‐preserved Big Data analysis) to satisfy the service. In order to achieve these important aspects, the VDP architecture is described along with roles/relations of technologies and concepts leveraged to and data sources considered in the platform. To explore the realisation possibility of the proposed approach in real disasters, a validation scenario considering the critical issues and details in a victim detection task is illustrated, and then appropriate techniques, which will be utilised in the proposed VDP, and its justifications are discussed. Finally, we debate how the techniques are harmonised in the VDP and what the challenges are.